THU0099 Myeloid sirtuin 6 deficiency accelerates experimental and human arthritis by increasing macrophage infiltration into synovium - Suh, Y.S.; Cheon, Y.-H.; Kim, M.Y.; Woo, S.J.; Noh, H.S.; Park, B.-H.; Lee, S.-I. (Annals of the rheumatic diseases, 2018)
BackgroundRheumatoid arthritis (RA) is an autoimmune inflammatory disease of the joints and is characterised by immune cell infiltration, synovial hyperplasia, and destruction of cartilage and underlying bone 1. Myeloid derived monocytes and macrophages secrete a variety of cytokines such as tumour necrosis factor-α (TNF-α), interleukin (IL)−1β and IL-6, all of which perpetuate and amplify the vicious cycle of chronic inflammatory pathways 2. Indeed, macrophage numbers in the synovium and serum levels of monocyte-derived cytokines correlate well with clinical symptoms and degree of joint damage in RA 3.ObjectivesWe recently reported that myeloid sirtuin 6 (Sirt6) is a critical determinant of phenotypic switching and the migratory responses of macrophages 4. Given the prominent role of macrophages in rheumatoid arthritis (RA) pathogenesis 5, we tested whether myeloid Sirt6 deficiency affects the development and exacerbation of RA.MethodsArthritis was induced in wild type and myeloid Sirt6 KO (mS6KO) mice using collagen-induced and K/BxN serum transfer models. Peripheral blood mononuclear cells (PBMC) and synovial fluid macrophages were obtained from patients with RA and osteoarthritis and used for comparisons of Sirt6 expression and inflammatory activities.ResultsBased on clinical scores, ankle thickness, pathology and radiology, arthritis was more severe in mS6KO mice relative to wild type with a greater accumulation of macrophages in the synovium. Consistently, myeloid Sirt6 deficiency increased the migration potential of macrophages toward synoviocytes-derived chemoattractants. Mechanistically, Sirt6 deacetylates forkhead box protein O1 to trigger its nuclear export and proteasomal degradation. Lastly, PBMC and macrophages isolated from RA patients exhibited lower Sirt6 expression compared with those from osteoarthritis patients or healthy subjects and their Sirt6 activity was inversely correlated with disease severity of the patients.ConclusionsOur data identify a role of myeloid Sirt6 in clinical and experimental RA and suggest that myeloid Sirt6 may be an intriguing therapeutic target.References[1] Ospelt C. Synovial fibroblasts in 2017. RMD Open 2017;3(2):e000471.[2] Gierut A, Perlman H, Pope RM. Innate immunity and rheumatoid arthritis. Rheum Dis Clin North Am2010;36(2):271–96.[3] Kinne RW, S tuhlmuller B, Burmester GR. Cells of the synovium in rheumatoid arthritis. Macrophages. Arthritis Res Ther2007;9(6):224.[4] Lee Y, Ka SO, Cha HN, et al. Myeloid sirtuin 6 deficiency causes insulin resistance in high-fat diet-fed mice by eliciting macrophage polarization toward an M1 phenotype. Diabetes2017;66(10):2659–68.[5] Lee HS, Ka SO, Lee SM, et al. Overexpression of sirtuin 6 suppresses inflammatory responses and bone destruction in mice with collagen-induced arthritis. Arthritis Rheum2013;65(7):1776–85.Disclosure of InterestNone declared